Effects of Waste Polypropylene Additive on the Properties of Bituminous Binder - Ahmedzade, Perviz; Demirelli, Kadir; Gunay, Taylan; Biryan, Fatih; Alqudah, Omar (Elsevier Science Bv, 2015)
In this study, a polymer which have a content of 80% wasted polypropylene and other materials, such as maleic anhydride and styrene known as compatible with bitumen was synthesised and employed as a modifier in bitumen. After the polymer (PPr) synthesizing, base and polymer modified bitumens were investigated by means of florescent microscope, penetration, softening point, rotational viscometer (RV) and dynamic shear rheometer (DSR) tests. The results indicated that PPR modifier provides an increased stiffness for bitumen. For instance, the binder having % 6 PPR has a penetration of 27 dmm, softening point value of 76 degrees C, viscosity of 687.5 cP whereas base bitumen has a penetration of 62dmm, softening point of 50.5 degrees C and viscosity of 412 cP. Stiffening effect of the PPr was also approved by complex modulus (G*) values in DSR tests. Better viscoelastic behaviour was observed by means of DSR test after the modification. In addition to importance of employing waste polymers in pavements in terms of economic and environmental care, the results indicate the positive effect of the waste polymer on the performance of bitumen and against of rutting in asphalt concrete. (C) 2015 The Authors. Published by ELsevier B.V.
2nd International Materials, Industrial, and Manufacturing Engineering Conference, MIMEC2015 -- FEB 04-06, 2015 -- Bali, INDONESIA
Keywords: Bituminous materials; Modification; Waste polypropylene; Polymer synthesis; Performance of bituminous binders